Deoxyribonucleic Acid Synthesis in recA and recB Derivatives of an Escherichia coli K-12 Strain with a Temperature-Sensitive Deoxyribonucleic Acid Polymerase I - Monk, M. (1973)
recA and recB derivatives of a strain of Escherichia coli with a temperature-sensitive deoxyribonucleic acid (DNA) polymerase I (polA12) are inviable at high temperature, but continue to incorporate (3)H-thymine into DNA for extended periods. The DNA made in pulse-chase experiments at high temperature in the polA12 parent and its double-mutant derivatives has been examined by alkaline sucrose gradient sedimentation analysis. The low-molecular-weight DNA fragments made during short pulses were joined at the same rate in each strain. Furthermore, the resulting high-molecular-weight DNA was of the same size in each case and was stable for at least 50 min. It is concluded that the inviability of the double mutants is due neither to a defect in converting low-molecular-weight DNA intermediates to high molecular weight nor to the presence of unrepaired random breaks in their DNA.